KEBIASAAN MAKAN PADA WANITA USIA SUBUR PENYEBAB PENYAKIT GASTRITIS DI DESA KEKAITKABUPATEN LOMBOK BARAT - Mariatul Qibtiah; Murtiana Ningsih (JURNAL SANGKAREANG MATARAM, 2016)
Digestive tract disease like gastritris attack more women than men; on women especially for productive women aged 20-44 years old. The result of interview toward 10 productive women at Kekait village Gunungsari district West Lombok Regency who got gastritis. It is because of unqualified dietary habit wich related to frequency, time and type of food that can cause stomach irritation. This study was aimed to know the relationship between dietary habit on productive women aged 20-44 years old and gastritis at Kekait village Gunungsari district West Lombok Regency in 2015. This study is surveyanalytic and case control if observed from time of research. Comparison between case and control 1;1, case sample determination by non probably method through saturated sampling, whereas control sample determination by quota sampling, namber of women sample in the amount of 74 productive women aged 20-44 years old. Instrumen for data collecting is questionnaires and result of respondents’ visitation to Gunungsari Public Health Center. The result of study by chi-square statistic test showed p value< α (0,017 < 0,05). The conclusion is there was a relationship dietary habit on productive women aged 20-44 years old and gastritis at Kekait village Gunungsari district West Lombok Regency in 2015. The suggestion for productive women aged 20-44 years oldshould be aware toward gastritis that relate to dietary habit by eating regularly, type and amount of food.